Analisis Lirik Lagu “Nia Anak Surga” Karya Erwin Chan Menggunakan Pendekatan Mimetik - Beby Anjelika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Literary work is an expression of the representation of the author's mind using language as a medium, where the human or author's feelings here are personal in the form of experiences, thoughts, feelings, ideas, enthusiasm and beliefs which are formed in a picture of life that can brings out the charm that uses language tools in written form. According to Teeuw (1988:23) in (Asria Fera Nurnazilia et al., 2022) literature comes from the root word